Tourist experience of nature in contemporary China: a cultural divergence approach. Issue 3 (27th May 2017) - Cui, Qingming; Liao, Xiaohui; Xu, Honggang
Abstract : The study of Chinese nature tourism is a relatively independent research realm which adopts a cultural perspective to study the tourist experience. Chinese tourists are regarded as being accustomed to experiencing nature through associating it with high culture such as landscape poetry and paintings, calligraphy, and so on, and the impacts of traditional popular culture are seldom addressed. Yet, for the majority of Chinese, popular culture has significant influences on their behavior. From a cultural divergence approach, this paper chooses Huangshan Mountain as a case to investigate the way common Chinese people experience nature, and it is found that cultural impacts are differentiated, since neither cultures nor tourist groups are homogeneous. Specifically, tourists can be classified into classicists and folklorists according to whether they have professional knowledge about the traditional arts. As the majority of Chinese are folklorists and are largely neglected in the research, they are the main interest of this study. High culture has a weak impact on folklorists because they lack professional knowledge to associate with nature through high culture. It is popular culture that strongly influences folklorists' behaviors in their drawing farfetched analogies to nature and praying to nature.